(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
This paper compares and contrasts elements of Kierkegaard’s account of despair and Klein’s theory of the depressive position. It is argued that there are similarities in both theorists’ accounts of the work of personal maturation and self-development. At the same time, the important philosophical differences between existential and psychoanalytic perspectives on human being are acknowledged. The paper concludes with a case example illustrating how Kierkegaardian and Kleinian perspectives might offer complementary insights into the client’s experience and the therapeutic work.